The Latest Methods of Construction Design - Dynybyl, Vojtěch; Berka, Ondrej; Petr, Karel; Lopot, František; Dub, Martin (Springer International Publishing : Imprint: Springer, 2016)
This book is based on the 55th International Conference of Machine Design Departments 2014 (ICMD 2014) which was hosted by the Czech Technical University in September 2014. It features scientific articles which solve progressive themes from the field of machine design. The book addresses a broad range of themes including tribology, hydraulics, materials science, product innovation and experimental methods. It presents the latest interdisciplinary high-tech work. People with an interest in the latest research results in the field of machine design and manufacturing engineering will value this book with contributions of leading academic scientists and experts from all around the world.